Marx and Epicurus: Atom Dialectics and Clinamen: Contributions for a Freedom Philosophy - Blanco Rodríguez, Ricardo Alberto (Res Publica. Revista de Historia de las Ideas Políticas, 2024)
This paper aims to explain the reception of Epicurus´s atomism and the dialectical reinterpretation of clinamen theory in Karl Marx´s doctoral thesis of 1841, with the purpose of extracting some contributions to a theory of freedom. For this, the implications of the Marxian dialectical approach applied to the epicurean declination are analyzed in the light of the contributions of Schiller's philosophical thought and Ricoeur's hermeneutic phenomenology. Marx discovers in Epicurus a "science of atomistics", in which the clinamen is the formal self-determination of the atom with respect to matter; its internal law, by means of which opens the possibility of a human freedom that transgresses the determinism. An attempt is made to show that natural causality and freedom are not mutually excluding in an idealistic materialism such as the epicurean, in which, according to Marx's interpretation, idea and matter are integrated into a dialectical synthesis.